TRANSPUAN DALAM PUSARAN PEMBERITAAN MEDIA ONLINE LOKAL DI SIKKA - Gabriel Langga Gabirel Langga (MEDIAKOM, 2022)
Transpuan became an interesting phenomenon so that it became the object of news from the mass media in Indonesia by crediting transwomen. This is because the mass media does not have a diverse and inclusive perspective. As a result, transwomen are always ostracized in society due to news contrusion formed by the mass media.  In this study, researchers used qualitative research by analyzing the framing  of transwomen issues in the vortex of local online media coverage in Sikka Regency, East Nusa Tenggara using four local media, namely pojokbebas.com, florespedia.com, lenterapos.id and ekorantt.com.  In this study, researchers used Robert N. Entman's framing analysis model by analyzing the elements of defining the problem, estimating the cause of the problem, making moral choices and finally emphasizing resolution. With four elements, it is known the perspective or perspective of journalists in constructing transwomen news so that the news is chosen to be highlighted in the eyes of the public.  Objek in this study used news texts about local online media reporting related to transwomen in Sikka District. Researchuses two data sources, namely primary data and secondary data. The results of this study show that the four local media pojokbebas, florepedia, lenterapos.id and ekorantt in framing their news show that the four local media provide a positive news space for transwomen as well as space for transwomen to speak out. In addition, the four local media in Sikka District showedtheir partiality towards transwomen by framing the news in a friendly and inclusive manner.